Seroprevalence of Neospora caninum in dairy cattle in Bahia, Brazil - Gondim, LFP; Sartor, I. F.; Hasegawa, M.; Yamane, I (Elsevier B.V., 1999)
Sera collected from 447 dairy cattle on 14 dairy farms were tested for Neospora caninum antibodies by use of an immunofluorescent antibody technique. Positive reactions with titres greater than or equal to 1:200 were found in 63 (14.09%) of animals. Neospora positive sera were also tested for Toxoplasma gondii antibodies by using a commercial latex agglutination test. Antibodies to T. gondii were detected in 3 (4.76%) of 63 N. caninum positive sera. These results indicate that N. caninum infection is widespread among dairy cattle in Bahia state. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: Neospora caninum; antibodies; immunofluorescent antibody technique; cattle